The Use of Flashcards in Strengthening the Writing Skills of Descriptive Texts - Puspitasari, Andhika Dyah; Suroso, Eko; Saptaningsih, Sri Endah (Universitas Nurul Jadid Probolinggo, Indonesia, 2024)
This study aims to improve the descriptive writing skills of grade IX C students at SMP N 3 Kalibagor. Based on initial observations, it was found that students' writing skills were not optimal, as seen from low engagement and poor writing scores. The study employed classroom action research (CAR) in two cycles, each consisting of one session. The participants were the teacher and grade IX C students. Data was collected through observations, tests, and field notes, and analyzed both qualitatively and quantitatively. Qualitative data evaluated improvements in the learning process, especially teacher actions, while quantitative data measured student achievement after each action. Results showed an increase in the average student performance score, from 77.5% in Cycle I to 100% in Cycle II. This indicates that using flashcards effectively enhances students' descriptive writing skills. Additionally, flashcards not only strengthened students' writing skills but also improved teacher competence and student engagement. Teachers are encouraged to choose media that aligns with lesson content and student interests. The study suggests that using flashcards can boost student engagement in learning. Therefore, this research contributes to enhancing the quality of writing instruction in grade IX at SMP N 3 Kalibagor and can serve as a reference for other teachers seeking effective media to support students' writing skills.